ChemInform Abstract: One‐Pot Reactions of Nitroenamines with Anilines and Ethyl Glyoxylate. Issue 47 (6th November 2014) - Pilipecz, Mihaly V.; Scheiber, Pal; Vincze, Zoltan; Varga, Tamas R.; Toth, Gabor; Nemes, Peter
Abstract A novel three‐component method for the condensation of anilines, ethyl glyoxylate, and cyclic nitroenamines is described to yield multi‐substituted ethyl propiolates (IV).